Slovakia Catching-Up Regions : Prešov Region - Key Development Dynamics - World Bank Group (World Bank, Washington, DC, 2019)
Though the European Union (EU) is a development conversion machine for national economies, it is less so for subnational regions. EU accession countries have been catching up to regional averages in terms of economic development since they joined the union. The economic success of the accession countries reduced disparities in national GDP per capita, but since 2005 both EU-wide and in most individual countries the gap between most- and least-developed subnational regions has been widening. This suggests that in accession countries growth, and its benefits are concentrated in a few regions, mostly large cities and national capitals, while many areas fall further behind. Slovakia illustrates the difference between national convergence and subnational divergence. While Slovakia is considered one of the EU’s economic stars, it also has some of the union’s highest regional disparities. Slovakia’s impressive economic gains over the last two decades were led by Bratislava region, which in 2016 became the sixth richest region in the EU by GDP per capita. On the other hand, Eastern Slovakia, which includes Prešov, is among the poorest regions in the EU. This report on the Prešov region of Slovakia, reviews patterns of regional development in Slovakia, discusses opportunities and challenges of the Prešov region, and recommends policy actions for the region.